PENGARUH MODAL, TENAGA KERJA DAN LAMA USAHA TERHADAP PENDAPATAN USAHA WARUNG SEMBAKO DI KECAMATAN PENEBEL KABUPATEN TABANAN - Ida Ayu Sintha Agustina; I Nyoman Widhya Astawa; Ni Nyoman Kasih (Universitas Mahendradatta, 2023)
Limited job opportunities make people innovate to open their own businessopportunities to meet their daily needs and other needs. Trading/opening a shopis one of the business opportunities that can be undertaken in order to be able tomeet all needs, as is the case with groceries traders/stalls in Penebel District,Tabanan Regency. The purpose of this research is to find out how the influence ofcapital, labor, and length of business either partially or simultaneously on theincome of the Grocery Warung Business in Penebel District, Tabanan Regency.Based on the results of SPSS calculations, the results of capital, labor, and lengthof business have a partial and simultaneous positive and significant effect onRevenue from Grocery Stalls in Penebel District, Tabanan Regency Based on the conclusions from the research results, it can be suggested that theGrocery Warung Business can increase capital by utilizing financial institutions,increase knowledge about consumer tastes and behavior and continue tomaximize labor.